1986
DOI: 10.1111/j.2044-8260.1986.tb00682.x
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and endocrine changes in surgical patients

Abstract: There is a need for research to identify the relationship between psychological and endocrine responses to surgical operations, and to discover whether these responses differ with variations in practice between different settings. This preliminary study investigated 17 patients undergoing middle ear operations in two hospitals. Measurements included state anxiety, Recovery Inventory, cortisol excretion and noradrenaline excretion. All were made pre-operatively and on three post-operative days. Recovery Invento… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
1

Year Published

1990
1990
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 0 publications
1
20
0
1
Order By: Relevance
“…Anderson (1987), utilising emotional and behavioural measures when surveying patients prior to cardiac surgery concluded information alone did not reduce anxiety although it did help to increase feelings of control. Salmon et al (1986) and Salmon (1992a) following a study of 17 patients undergoing surgery and general anaesthesia suggested forced compliance with a pre-operative educational programme actually led to an increase in anxiety.…”
Section: Indicators Against Information Provisionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anderson (1987), utilising emotional and behavioural measures when surveying patients prior to cardiac surgery concluded information alone did not reduce anxiety although it did help to increase feelings of control. Salmon et al (1986) and Salmon (1992a) following a study of 17 patients undergoing surgery and general anaesthesia suggested forced compliance with a pre-operative educational programme actually led to an increase in anxiety.…”
Section: Indicators Against Information Provisionmentioning
confidence: 99%
“…A number of studies have strongly suggested that forcing an extended level of information onto all patients can prove detrimental (Janis 1958, Salmon 19861992a, Kerrigan et al 1993, Hawkshaw 1994, Lamarche et al 1998. A minimum of two levels of information is therefore highly recommended i.e.…”
Section: A) Differing Levels Of Information Provisionmentioning
confidence: 99%
“…Similar inconsistencies and contradictions exist in anumber of studies that examine the effect of psychological interventions on physiological and biochemical outcomes of surgery (Manyande et al, 1992; Salmon et al, 1986;Wolfer & Davis, 1970). Interest in these measures has been generated from observations that catecholamines are sensitive to emotional state (Salmon et al, 1986) and that psychic and physical stresses of major surgery have been shown to be potent stimuli of cortisol secretion (Mason, 1972;Price, Thaler, &Mason, 1957).…”
Section: What Does Surgical Preparanon Influence?mentioning
confidence: 92%
“…Interest in these measures has been generated from observations that catecholamines are sensitive to emotional state (Salmon et al, 1986) and that psychic and physical stresses of major surgery have been shown to be potent stimuli of cortisol secretion (Mason, 1972;Price, Thaler, &Mason, 1957). Hypersecretion of cortisol has also been associated with the rate and quality of surgical wound healing (schilling, 1983).…”
Section: What Does Surgical Preparanon Influence?mentioning
confidence: 98%
“…The discrepancy between emo tional and catecholamine response is also reflected by a lack of significant correlations between these sets of variables observed for both HC and LC at stress I and with placebo at stress II. Reports in the literature on the lack of relationships between catecholamine and emo tional responses to stress experiments [47][48][49] or to sur gery in patients [50,51] are as frequent as those which report positive correlations for experimental [52,53] and for operative stress [54,55], so that it must be con cluded that the two reactions are most probably not cau sally related. Rather, emotional reactions may reflect individually different appraisals of threat and prepared ness to admit emotional arousal yielding reports of lower stress induced increase in anxiety in HC than in LC in spite of their higher E responsivity to the chal lenge of stress II.…”
Section: Discussionmentioning
confidence: 99%